2015
DOI: 10.1080/14703297.2015.1093426
|View full text |Cite
|
Sign up to set email alerts
|

User acceptance of social learning systems in higher education: an application of the extended Technology Acceptance Model

Abstract: a department of computer Engineering, atilim university, ankara, turkey; b department of software Engineering, atilim university, ankara, turkey

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 20 publications
6
31
0
Order By: Relevance
“…There is a large number of research studies carried out on this subject in the educational field related to RA, as well as a high number of meta-analyzes of the different educational models which allow to verify that they offer validity and solidity to how the intention of developing use of different technological environments in subjects. Recently, this has also been confirmed when analyzed with the structural equation models [55][56][57][58][59][60][61][62][63][64][65].…”
Section: Information Collection Instrumentsmentioning
confidence: 64%
“…There is a large number of research studies carried out on this subject in the educational field related to RA, as well as a high number of meta-analyzes of the different educational models which allow to verify that they offer validity and solidity to how the intention of developing use of different technological environments in subjects. Recently, this has also been confirmed when analyzed with the structural equation models [55][56][57][58][59][60][61][62][63][64][65].…”
Section: Information Collection Instrumentsmentioning
confidence: 64%
“…The findings indicated age and employment status were significant factors in predicting students' adoption of m-LMS. Akman and Turhan (2017) examined the users' acceptance of social learning systems in higher education with an extended TAM. They found that perceived usefulness, security awareness and ethical awareness were significant predictors of users' behaviour towards using social learning systems.…”
Section: Adoption Of M-lmsmentioning
confidence: 99%
“…The TAM was specifically developed to predict and explain computer usage, and uses the TRA as a theoretical basis for establishing causal linkages between the constructs of PU, PEOU, ATU, behavioral intention to use, and actual use of technology. Many studies have integrated the TAM into their research models to analyze factors that influence the behavioral intention to adopt various ICTs in education, including mobile learning [37], [38], cloud computing at universities [39], [40], social media in higher education [41]- [43], electronic portfolios [44], the Line mobile app for English oral training [45], and massive open online courses [46].…”
Section: A Dgsmentioning
confidence: 99%
“…PEOU I find GeoGebra easy to use. [41], [42], [54] Learning to operate GeoGebra would be easy for me. It would be easy for me to become skillful at using GeoGebra.…”
Section: A Survey Instrumentmentioning
confidence: 99%
See 1 more Smart Citation